Apoptotic mechanism of apigenin and rutin in ER+- breast cancer cells, MCF-7 / Roziana Kamaludin - Kamaludin, Roziana (2015)
Two-third of breast cancer patients expressed estrogen receptors (ER)s and received endocrine treatment with anti-estrogens such as tamoxifen. Unfortunately, a significant number of patients developed intrinsic and acquired resistances against this treatment. To date, the precise mechanism of these resistances is still largely unknown and this eventually turned the attention towards natural compounds as the alternative choice. Hence, these present study is aimed to determine the anti-proliferative effect and the underlying mechanism of apigenin and rutin on ER+-breast cancer and control breast cells (MCF-7 and MCF-10A, respectively) in comparison to tamoxifen, as well as to determine the involvement of tumor suppressor gene and pro-apoptotic BAX, Caspase-3, Caspase-8 and Caspase-9; and anti-apoptotic BCL-2 in the apoptotic signaling pathways induced by apigenin and rutin in MCF-7 as compared to tamoxifen. The effect of flavonoids e.g., apigenin and rutin on the proliferation of estrogen receptor-positive- (ER+)-breast cancer and control breast cells, (MCF-7 and MCF-10A, respectively) in comparison with tamoxifen was determined using MTT proliferation assay. Antiproliferative mechanism was investigated using annexin V-FITC/PI staining and cellular DNA fragmentation assays. The involvement of pro-apoptotic BAX, Caspase-3, Caspase- 8 and Caspase-9; and anti-apoptotic BCL-2 in apoptosis signaling was determined using QuantiGene 2.0 Multiplex assay. Protein expression was determined using protein ELISA assay. Apigenin and rutin inhibited the proliferation of MCF-7 in dose dependent manner with IC50 of 34.34±0.00 |xM and 46.09±0.00 (xM, respectively. They were less cytotoxic to MCF-10, with only rutin had exhibited an IC50 of 94.14±0.01 (iM. Contrary, tamoxifen was non-selective to both cells with IC50 o f 30.66±0.00 |iM and 38.17±0.01 |iM (p<0 .0 1 , n=3), respectively. Furthermore, apigenin and rutin significantly enhanced the cytotoxicity of tamoxifen on MCF-7 by 17.66±2.22% (p<0.01, n=3) and 20.21±2.95% (p<0.01, n=3), respectively; while protecting MCF-10A by 19.07±1.29% (p<0.01, n=3) and 21.81±1.70% (p<0.01, n=3), respectively against its toxicity. Apoptosis was observed through morphological features seen from Annexin/PI staining and DNA fragmentation. BAX were upregulated by apigenin and rutin in MCF-7. BCL-2 was downregulated by apigenin- but not expressed in rutin treatment. Contrary, BAX and BCL-2 were downregulated by tamoxifen. Caspase-3 was upregulated by rutin but not apigenin, while Caspase-8 and Caspase-9 were upregulated by both treatments. Only Caspase-8 and Caspase-9 were upregulated by tamoxifen. Accordingly, apigenin and rutin enhanced the expression of BAX protein, but not tamoxifen. BCL-2 protein expression was reduced by tamoxifen, but no changes seen in apigenin and rutin treatments. Caspase-9 protein was enhanced in all three treatments. These findings provide the evidences, about the underlying molecular signaling of apigenin and rutin-induced apoptosis in MCF-7 were through the intrinsic pathway by upregulation of BAX and Caspase-9; contrary to tamoxifen. Moreover, these flavonoids might be suitable candidates to be used in combination with chemotherapy agents such as tamoxifen to enhance its efficacy by reducing its adverse effects.